(untitled) (Global Journal of Medical Research, 2023)
Objective To observe the outcomes of the use of both Angiotensin Receptor-Neprilysin inhibitor ARNI and sodium-glucose cotransport 2-inhibitor SGLT2Ii in terms of echocardiographic parameters clinical symptoms cardiovascular death and Heart failure hospitalization in patient with heart failure reduced ejection fraction HFrEF in the hard-to-reach rural area of Africa Background Angiotensin Receptor-Neprilysin inhibitor ARNI is preferred over angiotensin-converting enzymes inhibitor or an angiotensin II receptor blocker as foundation therapy for patients with heart failure with reduced ejection fraction to reduce the risk of cardiovascular death Heart failure hospitalization and Heart failure symptoms SGLT2 inhibitor Dapagliflozin and Empagliflozin is among the four foundation drugs in managing HFrEF